Effectiveness of Loving Pregnancy Massage To Quality Sleep,Pain and Anxiety on Mother Pregnant Trimester III - Etin Rohmatin; Sariestya Rismawati (Midwifery and Nursing Research, 2021)
Background: During the period of pregnancy the mother suffered various complaints which cause discomfort due to changes in the physical as well as changes in psychological . As for the changes in the physical that is often experienced when pregnant include pain back , cramping legs, shortness of breath , frequent urination and responses psychic who experienced mother Pregnant form of depression , stress, anxiety and disturbance to sleep such as insomnia or difficulty in start sleepingMethods: The study is a pre- experiment with the design of the study is One group pretest-posttest design with the use of questionnaires in in Region Work Puskesmas Purbaratu on month in January and February 2019. Taking the sample in the study is using purposive sampling which totaled 31 people. Analysis of the data is done by univariate and bivariate by using Kruskal Wallis test.Results: The sleep quality of pregnant women before doing massage was in the category of moderate sleep disorders as many as 20 people (64.5%) while after massage in the category of good sleep quality , there were 17 people (54.8%). The pain of a mother pregnant before do massage on the category of light that as many as 21 people (67.7%). After doing massage in the light category , there were 19 people (61.3% ). Anxiety in the mother pregnant before do massage on the category of light that as many as 21 people (71.0%). When do massage all respondents in a category does not exist anxiety that as many as 31 people (100%). Signfikansi more substantial than 0.05 (0.172 0.05) means that not there is a difference significant effectiveness loving pregnancy massage to the quality of sleep , pain and anxiety mother pregnant third trimester in Region Work Puskesmas Purbaratu City of Tasikmalaya in 2019.Conclusion: The results of testing the value of Chi Square table df = 2 5991 Chi-square count 3523 and the value Asymp.Sig ( asymtopic significance) sebesae 0.172, because signfikansi more substantial than 0.05 (0.172 0.05) then the hypothesis Ho accepted means no There is a significant difference in the effectiveness of loving pregnancy massage on the quality of sleep , pain and anxiety of third trimester pregnant women in the Tasikmalaya City Purbaratu Health Center Work Area in 2019.